Cytotoxic, clastogenic and genotoxic effects of cis-tetraammine(oxalato)ruthenium(III) dithionate on human peripheral blood lymphocytes (Acta Scientiarum. Biological Sciences, 2020)
There is a concern about stablishing the clinical risk of drugs used for cancer treatment. In this study, the cytotoxic, clastogenic and genotoxic properties of cis-tetraammine(oxalato)ruthenium(III) dithionite - cis-[Ru(C2O4)(NH3)4]2(S2O6), were evaluated in vitro in human lymphocytes. The mitotic index (MI), chromosomal aberrations (CA) and DNA damage by comet assay were also analyzed. The MTT test revealed that the ruthenium compound showed a slight cytotoxic effect at the highest concentration tested. The IC50 value for the compound after 24 hours of exposure was 185.4 µM. The MI values of human peripheral blood lymphocytes treated with 0.015, 0.15, 1.5 and 150 µM of cis-[Ru(C2O4)(NH3)4]2(S2O6) were 6.1, 3.9, 3.2 and 0.2%, respectively. The lowest concentration, 0.015 µM, did not show any cytotoxic activity. The CA values for the 0.015, 0.15 and 1.5 µM concentrations presented low frequency (1.5, 1.6 and 2.3%, respectively), and did not express clastogenic activity when compared to the negative control, although it was observed clastogenic activity in the highest concentration tested (150 µM). The results obtained by the comet assay suggest that this compound does not present genotoxic activity at lower concentrations. The results show that cis-[Ru(C2O4)(NH3)4]2(S2O6) has no cytotoxic, clastogenic or genotoxic in vitro effects at concentrations less than or equal to 0.015 µM. This information proves as promising in the treatment of cancer and is crucial for future trials.